Vliv zelených střech na cenu objektu - Honusová, Kateřina (Vysoké učení technické v Brně. Fakulta stavební, 2022)
Tato práce je zaměřena na promítnutí zelených střech do ceny celého objektu rodinného domu. První část práce se zabývá popisem střešních konstrukcí a zelených střech (typy, vrstvy, vlastnosti). Následně jsou předvedeny různé typy nákladové cenotvorby (ocenění objektu, střešních konstrukcí) včetně rozdílných způsobů vypočtu obestavěného prostoru. Nakonec jsou zjištěné ceny střech dosazeny do ceny objektu. Stěžejní pro tuto práci je vypracování dílčích položkových rozpočtů na různé skladby zelených střech. Cílem této práce je zjištění, o kolik procent se navýší cena objektu, pokud se investor rozhodne pořídit tuto ekologii prospívající konstrukci.

This thesis is focused on the effect of green roofs and their impact on the final cost of a family house. First part of the thesis decribes different types of roofs, with a special emphasis on green roofs (including their types, layers, properties). Second part involves multiple types of pricing (house, roofs) and calculations of volumes of buildings. Final part discusses the prices of green roofs and their share in the price of the whole building. Creation of budgets is one of the most precise pricing strategies in civil engineering. Proper estimation of the budget of green roofs therefore played a vital role in developing results section of this bachelor thesis. The aim of this thesis is to evaluate the increase in price caused by this eco friendly contruction.
The influence of green roofs on the price of the building
Keywords: Zelená střecha; cena; střecha; stavba; cenotvorba; náklady; rozpočet; Green roofs; price; roofs; building structures; pricing; costs; budget